Optimalisasi Lahan Pertanian Perkotaan Melalui Pengembangan Budidaya Mina Padi Sebagai Upaya Pelestarian Pertanian Berkelanjutan - Luh Putu Kirana Pratiwi; Made Budiasa (Jurnal Ecocentrism, 2021)
The very high land degradation has resulted in the Denpasar City Government designing the establishment of the Sustainable Subak Area through a green line regulation in order to realize sustainable food agricultural land. In the context of optimizing the narrow agricultural land in urban areas, technological innovation is carried out from only rice farming to fish rice agricullture. The purpose of this study was to analyze the increase in rice farming income after the development of rice minarets and to synthesize efforts to conserve sustainable agriculture in an effective integrated fice rice agriculture. The method of analysis in this study was carried out quantitatively, namely feasibility analysis and qualitatively through qualitative descriptive. The results showed that fish rice farming has a higher level of feasibility when compared to the previous rice farming business. The net income of fish rice business is Rp. 7,165,250,- (35.29%), with an R/C ratio of 2.97. Sustainable conservation efforts in fish rice integrated agriculture are carried out through land improvement management, increasing added value, and strengthening institutional cooperation.